The importance of introducing cover crops in conventional agriculture - Ristakjovska, Shirgovska, B.; Prentovikj, T. (Macedonian Journal of Ecology and Environment, 2021)
As a consequence of the continuous world population amplification in the last century, agricultural production became intense by excessive mineral fertilizers, pesticides, irrigation, and the practice of continuous cultivation of the same soil. It has a negative impact on the soil’s physical, chemical, and biological properties, as a part of the natural environmental resources. Employing cover crops in conventional agriculture has numerous benefits: conservation of soil, surface and groundwater, benefits to the subsequent main plant cultivation in the crop rotational system, and protection of wildlife and biodiversity. Against many benefits, they could have some limitations due to farmers’ lack of knowledge, labor and organizing skills for proper timeline and management for all agricultural operations, and lack of machinery for planting and terminating cover crops mechanically. In the Republic of North Macedonia, because of a decline in animal production and reduced availability of organic fertilizers, there is a need to introduce alternative organic manures. In general, there is a lack of thorough studies for the appropriate selection of plant species or their mixture determined by our agro-ecological conditions, as well as the purpose of their use. Additionally, there is a need to strengthen the knowledge and information-sharing mechanisms with Macedonian farmers.
Keywords: cover crops, sustainable agriculture, soil and water conservation, organic manure